Christianity in a revolutionary age ; v. 5 a history of Christianity in the nineteenth and twentieth centuries - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1970)
Contents : v. 5 : The twentieth century outside Europe : the Americas, the Pacific, Asia and Africa : the emerging world Christian community. Includes bibliographical references and index.
First edition published 1958, New York, Harper and Row.
Keywords: Church history -- 20th century